2010
DOI: 10.3390/ph3072111
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinases as Drug Development Targets for Heart Disease Therapy

Abstract: Protein kinases are intimately integrated in different signal transduction pathways for the regulation of cardiac function in both health and disease. Protein kinase A (PKA), Ca2+-calmodulin-dependent protein kinase (CaMK), protein kinase C (PKC), phosphoinositide 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) are not only involved in the control of subcellular activities for maintaining cardiac function, but also participate in the development of cardiac dysfunction in cardiac hypertrophy, diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 242 publications
(295 reference statements)
0
27
0
Order By: Relevance
“…Finally, KinMap supports a minimalistic text input for less sophisticated annotations. For example, the following concise syntax annotates eight kinases potentially involved in cardiomyopathy [15]:…”
Section: Methodsmentioning
confidence: 99%
“…Finally, KinMap supports a minimalistic text input for less sophisticated annotations. For example, the following concise syntax annotates eight kinases potentially involved in cardiomyopathy [15]:…”
Section: Methodsmentioning
confidence: 99%
“…The mitogen‐activated protein kinases (MAPKs), a group of serine‐threonine kinases, are involved in regulating several signaling pathways that are crucial for the integration of mitogenic or apoptotic signals in cells (Papa et al, ; Yoshizumi et al, ). MAPKs regulate many important biological activities by influencing various cellular processes, namely, transcription, cell proliferation and survival, cell differentiation, inflammation, induction of apoptosis, and malignant transformation (Dhalla and Müller, ). They are classified into three major groups, the extracellular signal‐regulated kinases (ERKs), the c‐Jun N‐terminal kinases (JNKs) and the p38‐MAPK (Dhalla and Müller, ).…”
Section: Introductionmentioning
confidence: 99%
“…MAPKs regulate many important biological activities by influencing various cellular processes, namely, transcription, cell proliferation and survival, cell differentiation, inflammation, induction of apoptosis, and malignant transformation (Dhalla and Müller, ). They are classified into three major groups, the extracellular signal‐regulated kinases (ERKs), the c‐Jun N‐terminal kinases (JNKs) and the p38‐MAPK (Dhalla and Müller, ). They operate in cells through a well‐organized three‐tier module system, but with abundant cross talks between the modules ( reviewed in Manna and Stocco, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, such genetic events noticed in cancer are also observed in autoimmune disorders, in which approximately 90% of the causal variants are non‐coding, and most map to immune cell enhancer regions . Given the central role in cellular signaling of kinases in the heart and many other organs aside from cancers, accumulating pharmacological and pathological evidence has revealed that kinases are also promising drug targets for numerous non‐oncological indications . The successful approval of tofacitinib for the treatment of arthritis is a typical example, although the exact mode of action of tofacitinib in the setting of autoimmune disease has yet to be unraveled .…”
Section: Research Gaps Challenges Perspectives and Opportunities Tmentioning
confidence: 99%